Epidemiology of Helicobacter pylori infection in asymptomatic children: a prospective population-based study from the Czech Republic. Application of a monoclonal-based antigen-in-stool enzyme immunoassay - Sýkora, Josef; Siala, Konrad; Varvařovská, Jana; Pazdiora, Petr; Pomahačová, Renata; Huml, Michal (Helicobacter, 2009)
BACKGROUND: Acquisition of Helicobacter pylori occurs mainly in childhood and is significantly influenced by geographical variations. The aim of this study is to evaluate the prevalence of H. pylori infection in a population-based sample of asymptomatic children in the Czech Republic. Furthermore, this study aims to identify potential risk factors associated with this infection. MATERIALS AND METHODS: A prospective, cross-sectional, population-based study was undertaken in 1545 asymptomatic Czech children (aged 0-15 years; male 49.3%). Active H. pylori infection was diagnosed by monoclonal antibody-based antigen-in-stool enzyme immunoassay. Socio-demographic details of each subject were analyzed using a self-administered standardized questionnaire. Multiple regression analysis was performed. RESULTS: Overall, 7.1% of asymptomatic children were diagnosed with H. pylori infection. Of the infected children, 5.8% lived in the general population. A positive association was found with increasing age, although not with gender. Independent risk factors associated with H. pylori infection in our pediatric population were: the number of children in a household (odds ratio [OR] 4.26; confidence interval [CI] 1.91-9.80); lack of formal education of fathers (OR 0.23; CI 0.18-0.64) and institutionalized children (OR 6.33; CI 2.25-26.50). CONCLUSIONS: This study of a large cohort of children demonstrated that, independent of gender, H. pylori infection in the Czech Republic is among the lowest reported in Europe. Socioeconomically disadvantaged children, unfortunately, are still at risk of harboring this potentially preventable infection in this low-prevalence region.
Keywords: Infant; Adolescent; infekce vyvolané Helicobacter pylori; Male; lidé; ELISA; Humans; Child; Enzyme-Linked Immunosorbent Assay; Prospective Studies; Feces; Child, Preschool; Czech Republic; průřezové studie; mužské pohlaví; kojenec; dítě; prospektivní studie; Helicobacter Infections; Cross-Sectional Studies; Česká republika; ženské pohlaví; mladiství; feces; Female; předškolní dítě; Helicobacter pylori